Task Forces on Housing and Urban Development III Management of Urban Development - Planning Commission (Planning Commission, 1983)
In this Report, therefore, considering its pioneering character, we have dealt with concepts and issues in a selective manner and have simultaneously attempted to relate these to the practices and principles as hitherto available in the country. In our Report there are statements of emphases rather than explicit choices; we have talked about management issues in areas, which according to our opinion, are of importance and priority, indicating the opportunities and the scope of intervention available.
Planning Commission, Government of India